2012
DOI: 10.1186/2044-7248-1-12
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the shape symbolism of the taste, flavour, and texture of foods and beverages

Abstract: Consumers reliably match a variety of tastes (bitterness, sweetness, and sourness), oral-somatosensory attributes (carbonation, oral texture, and mouth-feel), and flavours to abstract shapes varying in their angularity. For example, they typically match more rounded forms such as circles with sweet tastes and more angular shapes such as triangles and stars with bitter and/or carbonated foods and beverages. Here, we suggest that such shape symbolic associations could be, and in some cases already are being, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 86 publications
(69 citation statements)
references
References 57 publications
2
66
0
1
Order By: Relevance
“…Another plausible explanation is that participants might have found the 71% chocolate to taste more acidic and confounded acidity in the chocolates with bitterness (e.g., [34]). Furthermore, it is plausible that the crystalline structure 1 , and therefore the mouthfeel, of the chocolates could have varied across samples. Although, as the chocolates were produced in the workshop of a master chocolatier, it is likely that chocolate texture was consistent across all the samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another plausible explanation is that participants might have found the 71% chocolate to taste more acidic and confounded acidity in the chocolates with bitterness (e.g., [34]). Furthermore, it is plausible that the crystalline structure 1 , and therefore the mouthfeel, of the chocolates could have varied across samples. Although, as the chocolates were produced in the workshop of a master chocolatier, it is likely that chocolate texture was consistent across all the samples.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that people can reliably match basic tastes to shapes with varying degrees of angularity (see [1], for a review). Most prominent amongst these correspondences is the association between round shapes and sweetness [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Specific contextual variables include, but are not limited to, background music [22]; the size, weight, and composition of cutlery [23]; a product's packaging [24]; colour lighting [25]; and menu item naming [26].…”
Section: Introductionmentioning
confidence: 99%
“…Noteworthy, other studies have shown that the shape of a plate and food (when 94 it is round as compared to angular) can influence participants' sweetness ratings of the food 95 (resulting in people rating the food as tasting sweeter, see Fairhurst,Pritchard,Opsina,& 96 Deroy, 2015, see also Piqueras-Fiszman, Alcaide, Roura, & Spence, 2012). 97…”
Section: Concentrations 83mentioning
confidence: 99%